ПІДВИЩЕННЯ ДИНАМІЧНИХ ХАРАКТЕРИСТИК ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК, ЗНАЧНО ВІДДАЛЕНИХ ВІД ІСКРОЕРОЗІЙНОГО НАВАНТАЖЕННЯ - Супруновська, Н.І.; Щерба, М.А.; Розіскулов, С.С.; Синицин, В.К. (Інститут електродинаміки НАН України, Київ, 2022)
The paper identifies the features of the influence of the characteristics of different connecting conductors on the dynamic characteristics of electric discharge installations (EDIs), which are distant significantly (several meters) from the spark-erosion load. In the electric spark production of dispersed powders, such a load is the interelectrode gap (IEG) in the technological dispersion apparatus (TAD), filled with a layer of metal granules and a low-conductive (preferably dielectric) flowing liquid. The influence of the design parameters of such long connecting conductors as twisted pair, litzendraht with bifilar winding of conductors and coaxial cable on the dynamic characteristics of the indicated EDIs (including on the average rates of rise and fall of the discharge pulse current) is experimentally investigated. It is substantiated that the use of power coaxial cables with modern cross-linked polymer electrical insulation is practically the most expedient for connection of significantly distant TAD under the condition of insignificant (up to 0.5 μH) self-inductance of EDIs. References 11, figures 4, tables 3.